PERANCANGAN TAS MEJA ERGONOMIS SEBAGAI PENUNJANG FASILITAS WORK FROM ANYWHERE - Tjahjaindra, Jordy; Widodo, Lamto; Ahmad (Jurnal Mitra Teknik Industri, 2024)
This ergonomic desk bag is useful as a product that makes it easier for people who work with high mobility so that a bag that functions as a storage area is combined with a foldable table and there are several features on the table, one of which is the height of the table legs that can be adjusted and in terms of materials choose materials that not too heavy so as not to make the user object. This product was made due to the lack of ergonomics of the table or the lack of availability of tables when people work outside the office. For this reason, this product is designed so that when carrying a bag, users can still use the table. The method used in this research is distributing questionnaires, the Ulrich and Eppinger Method, and the Analytical Hierarchy Process. . Ergonomic desk bag product design carries out the process of selecting the selected product then developing and implementing it on the user and the result is that the user can use the table when doing his work even though there is no table in that place.